E-LKPD BERBASIS LIVEWORKSHEET PADA MATERI BENTUK ALJABAR UNTUK PEMAHAMAN KONSEP MATEMATIKA - Syofiana, Mardiah; Firmania, Deya; Ristontowi; Risnanosanti; Bahasa Indonesia, Bahasa Indonesia; Bahasa Indonesia (Jurnal PEKA (Pendidikan Matematika), 2024)
This research is a Research and Development study using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with seventh-grade junior high school students as the subjects. The aim is to produce a learning media in the form of an Electronic Student Worksheet (E-LKPD) using the Liveworksheet main platform on the topic of algebraic forms. In the Analysis phase, information was gathered from teachers and students, revealing that the school only utilized printed books or worksheets and had not yet implemented technology-based learning media. In the Design phase, the plan for the E-LKPD product on the topic of algebraic forms was created, utilizing the Liveworksheet platform as the main medium, and Microsoft Word and Canva as supporting media. Development involved both product development and validation by three validators, resulting in a valid E-LKPD. The assessment of the feasibility of the learning media product by content experts averaged 4.31, categorized as Very Good, while media experts gave an average of 4.33, also categorized as Very Good. During the Implementation phase, a limited trial was conducted with seventh-grade junior high school students. Practicality was assessed with 83.73% of students rating it as Very Good, and 96% of teachers also rating it as Very Good. The Evaluation phase involved assessing each stage to ensure the development of a high-quality and accurate product.